Vancomycin-resistant enterococci colonization in a neonatal intensive care unit: who will be infected?. (1st November 2016) - Akturk, Hacer; Sutcu, Murat; Somer, Ayper; Acar, Manolya; Akgun Karapınar, Bahar; Aydin, Derya; Cihan, Rukiye; Ince, Zeynep; Çoban, Asuman; Salman, Nuran
Abstract: Objective : To determine the incidence of vancomycin-resistant enterococcus (VRE) colonization in our neonatal intensive care unit (NICU) over five-year period, rate of progression to VRE infection and associated risk factors. Methods : A retrospective analysis of a prospective surveillance for VRE colonization and health care-associated infections was made. Contact precautions were taken against colonization, although the application varied over the years due to repairs in the unit. Results : VRE rectal colonization was detected in 200/1671 neonates (12%) admitted to NICU. It showed great interannual variability from 1.9% to 30.3%. Sytemic VRE infection developed in 6/200 VRE-colonized patients (3%) within a median of 9 days (range: 3–58 days). The risk factors for VRE infection development identified in the univariate analysis were long hospital stay (≥30 days), necrotizing enterocolitis, surgical procedure, extraventricular drainage, receipt of amphotericin B and receipt of glycopeptides after detection of VRE colonization. Crude in-hospital mortality was higher in neonates who developed a systemic VRE infection ( p < 0.001). Conclusion : Maintaining physical conditions in the unit favorable for infection control and rational use of antibiotics are essential in the control of VRE colonization and resultant infections. Special attention should be directed to VRE-colonized babies carrying the risk factors.